A taxonomic revision of the genus Yelicones Cameron (Hymenoptera: Braconidae) from India with description of two new species - Gupta, Ankita; Pattar, Rohit; Kumar, H. M. Hemanth; Sushil, S. N. (Zootaxa, 2024)
The genus Yelicones Cameron, 1887 (Braconidae: Rogadinae) from India is revised. Two new species, Yelicones andamanensis sp. nov. and Y. elaeodendronicus sp. nov. are described and illustrated from India. Yelicones andamanensis sp. nov. was collected from Hut Bay, Little Andamans Island while Y. elaeodendronicus sp. nov. was reared from a pyralid caterpillar feeding on Elaeodendron glaucum (Rottb.) Pers in Bengaluru, India. The genus Yelicones is for the first time recorded from the Andaman & Nicobar group of islands. Both the species are compared with all the closely allied species from the Eastern Palearctic and the Oriental Regions. An illustrated key to the Indian species of the genus Yelicones Cameron is provided.